PERAN PENGHULU SEBAGAI MEDIATOR DALAM PENYELESAIAN SENGKETA PELANGGARAN TAKLIK TALAK PADA BP4 KECAMATAN DI KOTA MEDAN - Ahmad Kamil Harahap (P2WP MUI Sumatera Utara, 2026)
Abstract: This article examines the resolution of disputes concerning violations of ta‘l?q al-?al?q through Badan Penasihatan, Pembinaan, dan Pelestarian Perkawinan (BP4) at the Religious Affairs Office (KUA) in the Medan City District. In contrast to the classical fiqh conception, which regards conditional divorce as taking effect automatically upon the fulfillment of its stipulated condition, Indonesian positive law requires judicial proceedings through the Religious Court with the fulfillment of specific cumulative requirements, thereby creating a gap in public understanding. In this context, BP4 functions as a strategic non-litigation mediation space prior to court proceedings, with the marriage registrar (penghulu) serving as the primary mediator who integrates normative, sociological, and psychological approaches. Based on normative and empirical analysis, this study finds that the effectiveness of dispute resolution is strongly determined by BP4’s mediating role in bridging conflicts, reducing the escalation of divorce, and encouraging reconciliation. Accordingly, the optimization of BP4’s function and the role of the penghulu is key to building a more humane, preventive, and equitable marital dispute resolution system.